2021
DOI: 10.1051/e3sconf/202128407015
|View full text |Cite
|
Sign up to set email alerts
|

Ways of intensification of economic growth and activation of investment activities in order to ensure the economic security of the Russian Federation

Abstract: Macroeconomic dynamics is in the focus of attention of the scientific community due to the fact that it characterizes the key trends in the development of the national economy. The basic indicator in the system of national accounts is the gross domestic product (GDP), which in general form is the aggregate value of all goods and services produced within the national economy. GDP is widely used in the analysis of economic growth trends. Economic growth, creating conditions for it – the most important goal of ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 1 publication
0
14
0
Order By: Relevance
“…Based on the main aspects of trade and economic cooperation between Kazakhstan and Russia, it can be concluded that the leadership of the two countries is interested in deepening cooperation that objectively reflects the national interests of the states [13][14][15][16]. Almost all trade and transport routes that allow Kazakhstan to conduct broad economic cooperation with other countries pass through Russian territory.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the main aspects of trade and economic cooperation between Kazakhstan and Russia, it can be concluded that the leadership of the two countries is interested in deepening cooperation that objectively reflects the national interests of the states [13][14][15][16]. Almost all trade and transport routes that allow Kazakhstan to conduct broad economic cooperation with other countries pass through Russian territory.…”
Section: Resultsmentioning
confidence: 99%
“…In the immediate vicinity of the territory of Kazakhstan, as well as through its territory, there are transport highways connecting the European and Asian parts of Russia [15][16][17][18][19].…”
Section: Resultsmentioning
confidence: 99%
“…Growth of harmful emissions into the air Pollution of land along transport routes Growth in the number of car dumps [1] Population well-being Noise pollution Increased physical inactivity Growth and exacerbation of chronic nonspecific lung diseases Growth of introversion, need for solitude Methods to increase the attractiveness of urban public transport to reduce the number of personal transports have been considered most actively in the last couple of decades in European countries. Most of the research was carried out in the field of state regulation [2][3][4][5] and alternative environmentally friendly and healthy modes of transportation [6][7][8][9][10].…”
Section: Environmentmentioning
confidence: 99%
“…During this time, many information-oriented projects have been developed and implemented, among which electronic declaration of goods, remote provision of information about goods and vehicles planned for import in order to make a preliminary decision by customs authorities, as well as many other electronic services that significantly speed up customs formalities of participants in foreign economic activity: a convenient personal account, various payment systems simplifications in the form of special customs cards, which will allow spending less time on paying customs duties, taxes and other fees. Taking into account all of the above trends in the informatization of customs authorities, the authors of this paper propose to consider possible problems and solutions related to the conversion of some elements of the customs document flow [1][2][3][4][5][6][7][8], [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%